Biometric Model and Optimal Age for Realization in the Women's Triple Jump Discipline - Tereza Marinova (Editura Universitatii Transilvania din Brasov, 2023)
The purpose of the present study includes creating a biometric model of highly qualified female triple jump athletes, as well as establishing the optimal age for achieving a high sports result. The purposes are 1) Analysis of the anthropometric characteristics of 30 elite triple jumpers with personal achievements over 14.70 m.; 2) To analyze the development of the sports result in the age aspect. The analysis showed that the optimal age for achieving a high sports result in the triple jump discipline for women is on average 26 years. The female athletes studied by us have an average height of 176 cm, 62 kg. and their BMI is on average 19.6. The dynamics of the development of the sports result in terms of age in the athletes we studied gives us reason to conclude that achieving a high result at an early age is not a sign of future development, but we believe that this research of ours will contribute to improving the management and modeling of the training process in an age aspect.